2015
DOI: 10.1021/es5054286
|View full text |Cite
|
Sign up to set email alerts
|

Size Does Matter: Importance of Large Bubbles and Small-Scale Hot Spots for Methane Transport

Abstract: Ebullition (bubbling) is an important mechanism for the transfer of methane (CH4) from shallow waters to the atmosphere. Because of their stochastic nature, however, ebullition fluxes are difficult to accurately resolve. Hydroacoustic surveys have the potential to significantly improve the spatiotemporal observation of emission fluxes, but knowledge of bubble size distribution is also necessary to accurately assess local, regional, and global water body CH4 emission estimates. Therefore, we explore the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 45 publications
4
104
1
1
Order By: Relevance
“…The high rates of methane ebullition from Guntersville compared to CH 4 ebullition at the other reservoirs (Table 3) also support such possibility, because the funnel samplers integrated bubble-emissions over~24-h periods. Based on recent evidence of high within-reservoir spatial variability in ebullition [44], we suggest that an intensive seasonal and diel sampling effort of GHG emissions with increased spatial coverage at Guntersville would be very informative on processes related to CH 4 and CO 2 ebullitive emissions from hydropower reservoirs.…”
Section: Discussionmentioning
confidence: 90%
“…The high rates of methane ebullition from Guntersville compared to CH 4 ebullition at the other reservoirs (Table 3) also support such possibility, because the funnel samplers integrated bubble-emissions over~24-h periods. Based on recent evidence of high within-reservoir spatial variability in ebullition [44], we suggest that an intensive seasonal and diel sampling effort of GHG emissions with increased spatial coverage at Guntersville would be very informative on processes related to CH 4 and CO 2 ebullitive emissions from hydropower reservoirs.…”
Section: Discussionmentioning
confidence: 90%
“…8). DelSontro et al (2015) also reported a strong positive correlation between ebullition flux and bubble volume in open water and found that the largest 10 % of the bubbles observed in Lake Wohlen, Switzerland, accounted for 65 % of the CH 4 transport. According to the authors, large bubbles are disproportionately important because they contain exponentially more CH 4 with increasing diameter, rise faster, and have less time and a relatively smaller surface area to dissolve or exchange CH 4 with the surroundings (DelSontro et al, 2015).…”
Section: Spatial Pattern Of Ch 4 and Co 2 Fluxesmentioning
confidence: 88%
“…Since the Sauter Mean Diameter has been shown to be useful for estimating bubble dissolution rates for an entire bubble size distribution, the potential increase in Sauter Mean Diameter compared to measured data could be taken into consideration in dissolution calculations. For sites such as the one described in DelSontro () where bubbles over 2 mL (1.56 cm equivalent diameter) are found to contribute significantly to total ebullition flux, the sensor could be altered to contain a wider glass funnel stem which may improve large volume estimates. However, a larger funnel stem means fewer rising bubbles would be elongated, potentially reducing sensor accuracy as described under Potential Mechanism #6.…”
Section: Assessmentmentioning
confidence: 99%